A high efficiency stirling-type pulse tube refrigerator for cooling above 200 K. (15th January 2021) - Wang, Bo; Chao, Yijun; Zhao, Qinyu; Wang, Haoren; Wang, Yabin; Gan, Zhihua
Abstract: With the rapid development of infrared material and the serious threat of global warming and ozonosphere depletion, Stirling-type pulse tube refrigerators (PTRs) attract much attention for High Operation Temperature (HOT) infrared detectors cooling and refrigeration near ambient temperature as the advantages of oil lubrication free, compact structure, low vibration, high reliability and long life by eliminating moving parts at the cold end. A high efficiency Stirling-type PTR working above 200 K based on a detailed, time-saving hybrid design process is designed, fabricated and tested. A no-load cooling temperature of 99.8 K and a net cooling power of 181.3 W at 233 K are obtained with an input power of 500 W. The second law efficiency at 233 K and 154 K are 10.4% and 14.24% respectively, and the efficiency is about 50% higher than the conventional prediction of the PTRs at that temperature zone. The experimental results agree with the simulation well. The energy flows and losses in the PTR, the impedance matching between cold finger and compressor are discussed in detail. Numerical simulation indicates that the cooling power of the PTR will increase 30% when warm displacer is adopted as phase shifter. This work is a meaningful attempt to extend the working region of PTRs from cryogenic (<120 K) to near room temperature (>200 K). Highlights: The feasibility of PTR for cooling above 200 K is studied. The PTR could provide 181.3 W cooling power at 233 K with 500 W input power. The efficiency of the PTR above 200 K is about 50% higher than the prediction. Warm displacer could future improve the efficiency the PTR above 200 K.